IMPLEMENTASI PROFIL PELAJAR PANCASILA BERBASIS PROYEK PADA MATA PELAJARAN IPAS DI SEKOLAH DASAR - Susanti, Rista Dwi; Heri Maria Zulfiati; Daimul Hasanah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to understand the implementation of the Pancasila Student Profile in the IPAS subject for Grade V at the Ngento Public Elementary School, Pengasih, Kulon Progo. The approach used in this study is qualitative with a descriptive method. Data collection techniques include observation, interviews, and documentation. The results of this study indicate that the implementation of the Pancasila Student Profile at the school has positively contributed to shaping the students' character, as it includes the six dimensions of the Pancasila Student Profile. This aspect significantly contributes to students' problem-solving skills. To support the creativity of both students and teachers in innovating, the school has provided several facilities that students can use and participate in.